Fair value of land capital: methodical approaches and scenario modeling - Zavodiana, M. (Land Management, Cadastre and Land Monitoring, 2025)
The article examines the principles of forming the fair value of land capital under the conditions of profound transformations in Ukraine’s agricultural sector. It demonstrates that traditional approaches to land valuation no longer meet current challenges, as they fail to account for environmental threats, institutional changes, and risks associated with military actions. The author substantiates the feasibility of applying the fair value concept as a more flexible and adaptive approach suited to present-day realities. A modified model for determining the value of land capital based on net present value is proposed, which integrates the following factors: the share of land plots withdrawn from cultivation, annual net operating or rental income, losses due to demining and soil contamination (expenses or lost income), state compensations, discount rate, and risk premium. Scenario modeling was used to present several possible development trajectories—optimistic, pessimistic, pragmatic, and one excluding the effects of war. The results indicate that the speed of land resource recovery, the scope of state support, and the efficiency of managerial decisions are the key determinants for maintaining the economic potential of land capital. The developed methodological framework can be applied both for decision-making at the level of agricultural enterprises and territorial communities, as well as for improving state land policy in the context of post-war recovery. Keywords: land capital, fair value, market value, net present value, risk premium, discount rate, rental income, state compensations, humanitarian demining, soil contamination, post-war recovery, agricultural sector, land valuation, scenario modeling, investment attractiveness of land.